2011
DOI: 10.1038/mt.2011.133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apolipoprotein A-I in Rabbit Carotid Endothelium Protects Against Atherosclerosis

Abstract: Expression of atheroprotective genes in the blood vessel wall is potentially an effective means of preventing or reversing atherosclerosis. Development of this approach has been hampered by lack of a suitable gene-transfer vector. We used a helper-dependent adenoviral (HDAd) vector to test whether expression of apolipoprotein A-I (apoA-I) in the artery wall could retard the development of atherosclerosis in hyperlipidemic rabbits. Carotid arteries were infused with an HDAd expressing rabbit apoA-I or a "null" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 53 publications
4
68
0
Order By: Relevance
“…Limited lesion development in HDAdNull-infused carotids may explain why we detected only a modest effect of HDAd-expressed apolipoprotein (apo) A-I gene therapy on lesion size at 4 weeks (Flynn et al, 2011) and failed to detect any effect of HDAd-expressed interleukin-10 gene therapy on lesion size at either 4 or 8 weeks . Another limitation of this model is that exposure to Ad during lesion initiation immunizes the rabbit to Ad capsid proteins (Schulick et al, 1997).…”
Section: Introductionmentioning
confidence: 40%
See 4 more Smart Citations
“…Limited lesion development in HDAdNull-infused carotids may explain why we detected only a modest effect of HDAd-expressed apolipoprotein (apo) A-I gene therapy on lesion size at 4 weeks (Flynn et al, 2011) and failed to detect any effect of HDAd-expressed interleukin-10 gene therapy on lesion size at either 4 or 8 weeks . Another limitation of this model is that exposure to Ad during lesion initiation immunizes the rabbit to Ad capsid proteins (Schulick et al, 1997).…”
Section: Introductionmentioning
confidence: 40%
“…Accordingly, we began using HDAd to develop atheroprotective gene therapy in our rabbit carotid model. However, we found that lesions in fat-fed rabbit carotids infused with HDAdNull are much smaller than lesions in fat-fed rabbit carotids infused with FGAdNull, and that-unlike FGAdassociated lesions-HDAdNull-associated lesions regress spontaneously between 4 and 8 weeks after vector infusion Flynn et al, 2011). The small and transient character of atherosclerotic lesions in HDAdNull-infused carotids is likely because of the less inflammatory nature of HDAd (Wen et al, 2004).…”
Section: Introductionmentioning
confidence: 46%
See 3 more Smart Citations